2006
DOI: 10.1186/1475-2875-5-107
|View full text |Cite
|
Sign up to set email alerts
|

Topography and malaria transmission heterogeneity in western Kenya highlands: prospects for focal vector control

Abstract: Background: Recent resurgence of malaria in the highlands of Western Kenya has called for a more comprehensive understanding of the previously neglected complex highland vector ecology. Besides other drivers of malaria epidemiology, topography is likely to have a major effect on spatial vector and parasite distribution. The aim of this study was to determine the effects of topography on malaria spatial vector distribution and parasite prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
128
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(148 citation statements)
references
References 25 publications
16
128
4
Order By: Relevance
“…Three holo-endemic sites were located in lowlands: Kombewa (34°30′E, 0°07′N, 1,150–1,300 m asl); Miwani (0°07′S, 35°05′E, 1,100–1,200 m asl); and Rae (00°25′S 34°95′E, 1,143–1,200 m asl) in Kisumu County (Figure 1). Iguhu and Emakakha have flat shaped valleys, Kombewa, Rae and Miwani are in the flat lowland regions, while Marani has steep valleys [11]. Climate in western Kenya consists mainly of two seasons of rainfall, a long rainy season that is the peak of malaria transmission between March and May and a short one between October and November.
Figure 1Map showing the study sites in the western Kenya highlands.
…”
Section: Methodsmentioning
confidence: 99%
“…Three holo-endemic sites were located in lowlands: Kombewa (34°30′E, 0°07′N, 1,150–1,300 m asl); Miwani (0°07′S, 35°05′E, 1,100–1,200 m asl); and Rae (00°25′S 34°95′E, 1,143–1,200 m asl) in Kisumu County (Figure 1). Iguhu and Emakakha have flat shaped valleys, Kombewa, Rae and Miwani are in the flat lowland regions, while Marani has steep valleys [11]. Climate in western Kenya consists mainly of two seasons of rainfall, a long rainy season that is the peak of malaria transmission between March and May and a short one between October and November.
Figure 1Map showing the study sites in the western Kenya highlands.
…”
Section: Methodsmentioning
confidence: 99%
“…In the western Kenya highlands, anopheline larval habitats are generally restricted to the valley bottoms, especially during the dry season (Minakawa et al, 2005b;Mushinzimana et al, 2006;Githeko et al, 2012). Githeko et al (2006) classified study villages as 'valley-bottom', 'mid-hill' and 'hill-top' and found that vector density, EIR and malaria prevalence all decreased upslope. Similarly, Brooker et al (2004) and Kazembe (2007) found that altitude is a significant risk factor for malaria.…”
Section: Topographically-driven Surface Saturationmentioning
confidence: 97%
“…McWilliams et al (2007) used an adaptive Table 3 Potential impacts of climate change at a regional level (based on Githeko et al 2006) Place Potential effect…”
Section: Balancing the Environment And Human Health Issues: Adaptive mentioning
confidence: 99%